Water security in the polycrisis: between negative and positive tipping points - Scheffran, Jürgen (Frontiers in Water, 2025)
Water security is facing multiple stressors in the emerging polycrisis of the Anthropocene, with a great acceleration challenging planetary boundaries and human livelihoods. In a framework of interactions the hydrological cycle is connected to the Earth’s ecological and social systems, becoming a potential crisis multiplier through pathways in the water-food-energy nexus and the water-climate-conflict nexus. Water security balances protection of natural water resources and societal efforts to meet human needs, identify nexus tradeoffs and synergies, and facilitate transitions from negative to positive tipping points. Beyond simple narratives of water wars, various conflict types are considered, from water scarcity and abundance as conflict drivers to water as a weapon, target and casualty of conflict. To contain water-related tensions and strengthen cooperation in water distribution and control, investments and institutional mechanisms preserve the natural resource base, support technical and social innovations for efficient, sufficient, resilient, fair, peaceful and sustainable water use, and collaborate on integrated water sharing and trust building in environmental cooperation, conflict transformation and peacebuilding. Assessments and solutions are illustrated for local water systems and regional hot spots in Africa, Middle East, South, East and Central Asia.